Socio -Territorial Transformations of the Northeast Region of Uruguay (2000-2018) - Childe Pereira, Rodrigo Luan; Achkar Borras, Marcel; Freitas Scaraffuni, Gabriel; Webler Cancelier, Janete Webler Cancelier (Geografares, 2020)
This article aims to understand how socio-territorial transformations have been manifesting in the northeast region of Uruguay between 2000 and 2018. In this period, the territorial expansion of agribusiness through soy monoculture and forestry intensifies, which causes important changes in the productive, social, and landscape base. The objective is, on one hand, to describe quantitatively and in terms of changes in land use, the recent transformations in the agrarian territories of the region and, on the other hand, to understand the impacts of these processes on some social dynamics, especially in the migration of family producers and their families from the agrarian space to the urban one.  The methodology included a bibliographic and documentary review, the analysis of statistical data from the General Agricultural Census, and the analysis of land use through satellite images. The results show that monocultures linked to agribusiness have modified the agrarian structure and the use of the territory resulting in increasing pressure on the price of land, which puts the permanence of family producers at risk
Keywords: Territory; Agribusiness; Family producer